Zambia Education PER and PETS-QSDS at a Glance - World Bank Group (World Bank, Washington, DC, 2016)
Public Expenditure Review (PER) in Zambia addresses the efficiency and equity of the macrolevel policy framework, budget allocations, and budget execution for primary education; secondary education; technical education and vocational and entrepreneurship training (TEVET); and higher education. The Public Expenditure Tracking Survey (PETS) traces fund flows from the central government to schools in order to identify leakages and assess efficiency and effectiveness in the use of public funding. The Quantitative Service Delivery Survey (QSDS) examines the efficacy of spending, incentives oversight, and the relationship between those who contract for a service (for example, parents) and those who deliver it (schools and teachers).